2017
DOI: 10.1002/ijc.30853
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐methylation‐mediated repression of miR‐766‐3p promotes cell proliferation via targeting SF2 expression in renal cell carcinoma

Abstract: Aberrant expression of microRNA (miRNA) emerges as an important role in a wide range of human malignances, and further identification as well as validation of the change of these endogenous non-protein-coding transcripts is warranted. Here, we identify a novel epigenetic regulation of miR-766-3p and investigate its biological function as well as clinical significance in renal cell carcinoma (RCC). Bisulfate analysis elucidates that the promoter of miR-766-3p is highly methylated in RCC tissues compared to non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 44 publications
(79 reference statements)
6
46
0
Order By: Relevance
“…For instance, miR-766 was reported to promote cell proliferation in colorectal cancer by targeting SOX6 expression (12). In renal cell carcinoma, miR-766 overexpression attenuated cell-cycle progression by down-regulating SF2 expression (21). In this study, our results showed that miR-766 was up-regulated in HCC tissues and that up-regulation of miR-766 promotes the proliferation and metastasis of HCC cells by directly decreasing the NR3C2 expression.…”
Section: Discussionsupporting
confidence: 53%
“…For instance, miR-766 was reported to promote cell proliferation in colorectal cancer by targeting SOX6 expression (12). In renal cell carcinoma, miR-766 overexpression attenuated cell-cycle progression by down-regulating SF2 expression (21). In this study, our results showed that miR-766 was up-regulated in HCC tissues and that up-regulation of miR-766 promotes the proliferation and metastasis of HCC cells by directly decreasing the NR3C2 expression.…”
Section: Discussionsupporting
confidence: 53%
“…Expression of miR-766 is decreased in renal cell carcinoma, and low miR-766 expression is significantly correlated with the clinical stage. In addition, patients with renal cell carcinoma and low miR-766 expression exhibit poorer prognosis compared with those patients with high miR-766 expression (23). Conversely, miR-766 is overexpressed in lung adenocarcinoma (24) and colorectal cancer (25).…”
Section: Discussionmentioning
confidence: 99%
“…miR-766 has been well studied in numerous types of human cancer, including renal cell carcinoma (23), lung adenocarcinoma (24) and colorectal cancer (25). However, the expression status, specific roles and regulatory mechanisms of miR-766 in PTC remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Renal cell carcinoma (RCC) is one of the most aggressive human urological malignancies, accounting for 2%-3% of adult malignancies [15; 39]. One third of patients have metastatic lesions detected at primary diagnosis, and 30% eventually develop metastatic renal cell carcinoma (mRCC) after surgery [2]. Because of its resistance to radiotherapy and chemo-therapy, surgical resection remains the unique effective treatment [1; 25].…”
Section: Introductionmentioning
confidence: 99%